STRATEGI PEMASARAN STP (SEGMENTING, TARGETING, POSITIONING) PADA INDUSTRI KECIL BATIK TULIS HI KAMPOENG BATIK JETIS SIDOARJO - Shella Ayu Yunita; Joko Widodo; Hety Mustika Ani (STKIP PGRI Jombang, 2022)
This study aims to describe how the STP (Segmenting, Targeting, Positioning) marketing strategy is applied by the small industry of Batik Tulis HI in Kampoeng Batik Jetis, Sidoarjo Regency. This research is a descriptive study using a qualitative approach. Research subjects and informants, owners, employees and customers from small industries of Batik Tulis HI. Data collection methods used are interviews, observation, and documents. The data analysis of this research uses the stages of data reduction, data presentation, and drawing conclusions. The validity of the data from this study used a source triangulation technique. Based on the research conducted, the researcher concludes that the segmenting strategy carried out at Batik Tulis HI Sidoarjo is based on geographic, demographic, psychographic and behavioral segmentation. Geographical segmentation, the target area is Mojokerto, Pasuruan, Surabaya and even outside Java (Kalimantan, Sulawesi, etc.). The demographic segmentation includes civil servants, private employees, businessmen, socialite, and foreign guests, aged 40 years and over and indicated by more than adequate income and more dominant visitors coming to the female gender than the male gender. Psychographic segmentation, visitors who come mostly from the middle class with a lifestyle that follows the trend/fashionable. The main targeting target market is civil servants, private employees and entrepreneurs. Its target market strategy uses the same targeting strategy in which an industry adopts a mass marketing system. Positioning, by placing a brand image so that it impresses well in the minds of consumers and prioritizing distinctive service and quality by always improving quality.